Predictors of response to combined wake and light therapy in treatment-resistant inpatients with depression. (2nd September 2018) - Kragh, Mette; Larsen, Erik Roj; Martiny, Klaus; Møller, Dorthe Norden; Wihlborg, Camilla Schultz; Lindhardt, Tove; Videbech, Poul
ABSTRACT: There is growing evidence for combined chronotherapeutic interventions as adjunctive treatments for major depression. However, as the treatments can be demanding, we need to identify predictors of response. This study aimed to describe predictors of response, remission and deterioration in the short-term phase, as well as predictors of long-term response. The predictors investigated were gender, type of depression, severity of depression, treatment resistance, quetiapine use, general self-efficacy, educational level and positive diurnal variation. Follow-up data from 27 inpatients with moderate-to-severe depression participating in a chronotherapeutic intervention were analysed. As a supplement to standard treatment, they completed 3 wake therapy sessions in the first week, 30 min daily light treatment and sleep-time stabilisation in the entire 9-week study period. Patients had a significant decrease of depressive symptoms during the first 6 days measured by HAM-D6. At Day 6, 41% of the patients responded to the treatment and 19% fulfilled the criteria of remission. Deterioration by the end of wake therapy sessions was however not uncommon. In the short-term phase, mild degree of treatment resistance was associated with remission and low educational level associated with deterioration. Positive diurnal variation (mood best in the evening) was a predictor of both short-term and long-term response to combined wake and light therapy. Furthermore, patients with evening chronotypes (measured with morningness-eveningness score) were more responsive. Our results suggest that targeting the combined chronotherapeutic intervention at patients with positive diurnal variation and evening types is a viable option.